Art and Masonic culture in the Baroque Mexico - Fernández, Martha (2016)
Despite its importance, Freemasonry in the art of the Baroque Mexico is absent in historiography, but there are enough elements to believe that despite all the obstacles faced by, artists and society could be linked to culture since the end of the 17TH century and early 18TH century Masonic. Concepts such as the Great architect of the universe, the representation of the Saints crowned, the presence of iconographic symbols as square, compass and Plumb, as well as the portrait of a novohispano architect as a master mason, lead us to consider that possibility. All of this within a social and artistic context in which must take into account the trade crisis and the existence of a titled Brotherhood of our Lady of joys and Santos architects. In this article I present advances of a broader investigation that I'm developing on that important issue.